Efektivitas media pembelajaran berbasis Google Sites dalam meningkatkan pemahaman konsep siswa kelas X - Alan Mustapa; Jarot Tri Bowo Santoso (Universitas Negeri Surabaya, 2025)
Technological advancements have influenced the use of digital media in economics learning. Digital media is believed to provide an interactive and efficient learning experience while expanding access to learning resources. However, research on the effectiveness of Google Sites as an interactive learning medium remains limited, particularly for the topic of scarcity. This study aims to analyze the effectiveness of using Google Sites to enhance students’ understanding of scarcity concepts in tenth-grade classes. Using a descriptive qualitative method, data were collected through unstructured interviews, participatory observations, and document analysis of student assignments uploaded to Google Drive. The informants consisted of one economics teacher and 18 tenth-grade students at SMA Negeri 1 Ungaran. The findings indicate that Google Sites is effective in: (1) presenting scarcity materials visually and interactively, (2) increasing student engagement, and (3) supporting independent learning. The main challenges include internet dependency and the need for teacher training in digital content development. This study recommends integrating Google Sites with a flipped classroom model.